Predictors of In-Hospital Mortality among Patients with Pulmonary Tuberculosis: A Systematic Review and Meta-analysis - de Almeida, Carlos Podalirio Borges (Sci Rep, 2018)
Background: There is uncertainty regarding which factors are associated with in-hospital mortality among patients with pulmonary TB (PTB). The aim of this systematic review and meta-analysis is to identify predictors of in-hospital mortality among patients with PTB. Methods: We searched MEDLINE, EMBASE, and Global Health, for cohort and case-control studies that reported risk factors for in-hospital mortality in PTB. We pooled all factors that were assessed for an association, and presented relative associations as pooled odds ratios (ORs). Results: We identified 2,969 records, of which we retrieved 51 in full text; 11 cohort studies that evaluated 5,468 patients proved eligible. Moderate quality evidence suggested an association with co-morbid malignancy and in-hospital mortality (OR 1.85; 95% CI 1.01–3.40). Low quality evidence showed no association with positive sputum smear (OR 0.99; 95% CI 0.40–2.48), or male sex (OR 1.09, 95% CI 0.84–1.41), and very low quality evidence showed no association with diabetes mellitus (OR 1.31, 95% IC 0.38–4.46), and previous TB infection (OR 2.66, 95% CI 0.48–14.87). Conclusion: Co-morbid malignancy was associated with increased risk of in-hospital death among pulmonary TB patients. There is insufficient evidence to confirm positive sputum smear, male sex, diabetes mellitus, and previous TB infection as predictors of in-hospital mortality in TB patients.